Fenomena Perilaku Moral Siswa Selama Daring di SMA Negeri 2 Solok Selatan - Nadya Salsabillah; Isnarmi Moeis; Fatmariza Fatmariza; Junaidi Indrawadi (Journal of Civic Education, 2023)
This article aims to elucidate the various forms of student moral behavior observed during online learning, as well as to identify the underlying factors influencing such behavior both in the context of online learning and during the transition back to traditional classroom settings. The study explores diverse manifestations of student moral conduct, encompassing levels of honesty, discipline, and politeness. Employing a qualitative research design with a descriptive approach, data was collected at SMA N 2 Solok Selatan using purposive sampling for informant selection. The data gathering techniques encompassed interviews, documentation studies, and post-observation analysis. To ensure data validity, triangulation of sources was performed, and data was subsequently analyzed through collection, reduction, presentation, and conclusion stages. Findings revealed instances of student dishonesty during online learning, including plagiarism in friend's assignments, copying answers from the internet, and deceptive behavior towards parents. Additionally, students exhibited reduced politeness in their communication with teachers. The research also highlighted influential factors contributing to student moral behavior, attributing challenges in adjusting to the online learning system to both parents and teachers. The impact of this adaptation was observed in students' moral conduct during the transition back to conventional learning, manifesting as difficulty in completing assignments and a lack of self-confidence in offline learning settings.